Clinical and ethical challenges for emergency departments during communicable disease outbreaks: Can lessons from Ebola Virus Disease be applied to the COVID‐19 pandemic?. (5th May 2020) - Markwell, Alexandra; Mitchell, Rob; Wright, April L; Brown, Anthony FT
Abstract: EDs fulfil a frontline function during public health emergencies (PHEs) and will play a pivotal role during the COVID‐19 pandemic. This perspective article draws on qualitative data from a longitudinal, ethnographic study of an Australian tertiary ED to illustrate the clinical and ethical challenges faced by EDs during PHEs. Interview data collected during the 2014 Ebola Virus Disease PHE of International Concern suggest that ED clinicians have a strong sense of professional responsibility, but this can be compromised by increased visibility of risk and sub‐optimal engagement from hospital managers and public health authorities. The study exposes the tension between a healthcare worker's right to protection and a duty to provide treatment. Given the narrow window of opportunity to prepare for a surge of COVID‐19 presentations, there is an immediate need to reflect and learn from previous experiences. To maintain the confidence of ED clinicians, and minimise the risk of moral injury, hospital and public health authorities must urgently develop processes to support ethical healthcare delivery and ensure adequate resourcing of EDs.